Application of classification rules to Italian ports - Lupi, Marino; Farina, Alessandro; Pratelli, Antonio; Gazzarri, Alessandra (Promet - Traffic&Transportation, 2014)
In this paper, the existing rules commonly used for port traffic comparison are described. These rules provide weighting factors for each freight category in order to make them comparable and exploitable for port ranking. These rules are based on the value added concept related to port activities. Two new rules are proposed. The first is again based on the value added concept. The second rule is based on the assumption that ports not only create labour directly, through activities related to port operations, but they also play the role of “gates” for the existing economic activities of a region or a country, as a consistent quota of the overall international trade takes place by sea. This rule is based on the relationship among the trend of traffic volume of each freight category and the trend of the national GDP. The rules existing in the literature and the proposed new rules have been applied in ranking Italian ports; the results are discussed. The sensitivity of the ranking of Italian ports, to the different weighting rules, has been analysed.